PEMBERDAYAAN KESEHATAN MENTAL MASYARAKAT BERBASIS BIMBINGAN KONSELING MULTIKULTURAL - Arifin Hidayat; Fitri Khairani Siregar; Darwin Harahap; Fithri choirunnisa Siregar; Umi Khumairoh Nasution (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
The main problem addressed in this study is the low public awareness of mental health importance and the strong social stigma that still exists in multicultural areas such as Batahan, Mandailing Natal. The purpose of this study is to describe the process of community mental health empowerment through the application of a multicultural counseling approach that aligns with local values and cultural contexts. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observations, and document studies involving community members, traditional leaders, and professionals participating in the empowerment program. The results show that the implementation of multicultural counseling successfully enhances community awareness of mental health importance, strengthens individual coping mechanisms, improves social interactions, and increases community participation in sustainable mental health activities. These findings emphasize that integrating a multicultural approach into community mental health empowerment programs is highly effective, especially in culturally diverse regions like Batahan